Intervención educativa nutricional en el conocimiento alimentario de padres, hábitos alimentarios y estado nutricional de escolares de la I.E Experimental UNAP - 2022 - Baneo Shapiama, Lesly Janela (2023)
The present research work was carried out at the I.E. Experimental -UNAP was carried out at the Experimental School -UNAP, with the objective of determining the impact of a nutritional educational the impact of a nutritional educational intervention on parents' dietary knowledge, eating habits and nutritional nutritional status of elementary school children. The The study had a quantitative, quasi-experimental approach, with a pretest and post-test design, with a pretest and post-test design, with an experimental group and a control group. The data collection was longitudinal. The sample consisted of 91 students in the experimental group and 84 students in the control group. The instruments used were the food knowledge questionnaire, food consumption frequency questionnaire, and a nutritional evaluation card. The Chi-square test was used to test the research hypothesis. The results report that the parents' level of knowledge increased by 1.1%. Eating habits after the intervention increased by 6.6% in healthy eating habits. Nutritional status (NS) according to BMI/age increased from normal NS from 60.4% to 63.7%, and height/age from 94.5% to 95.6% of normal height; however, hemoglobin level decreased from 77.0% to 75.8%. In this sense, we say that at a 95% confidence level, the level of knowledge, eating habits and nutritional status according to BMI/age, height/age, had an impact after the nutritional educational intervention, with values of nutritional educational intervention, with p-values of 0.000, 0.012, 0.003, 0.000, likewise the EN according to hemoglobin level had a negative impact, with a p-value of 0.002, 0.012, 0.003, 0.003, 0.000. p-value of 0.003. The conclusion is that the nutritional education intervention is a strategy that allows that allows actions to be taken to improve the nutritional knowledge of parents knowledge of parents, and thus change to good food consumption habits and improve the nutritional status of their children. to good food consumption habits and improve the nutritional status of schoolchildren.